Global Climate Change Coverage in Malaysia Mainstream Newspapers - Nor Jijidiana, Azmi; Rahmat, Ghazali (2013)
Global Climate Change can affect human life and activities. The rising amount of natural disasters, the warming of the Earth and the melting of the icebergs are some examples of its effects. This study is conducted to analyze the coverage of global climate change issue in four Malaysia mainstream newspapers. The data for this study are collected from January 2008 to December 2010. A content analysis is conducted to identify the frequency of the articles related with global climate change, the articles length, the trend of newspaper coverage and the frames of the articles. The findings for this study will provide an understanding about the ways Malaysia mainstream newspapers provide the coverage about Global Climate Change and the audience reactions towards the issue. The findings also suggested that the coverage of global climate change is influenced by the events pertaining the issue. This can be observed from the trend of newspaper coverage. Finally, the result on the frames indicates that the most published topic in global climate change issue is public action to reduce the effects of global climate change and reduce the emissions of the greenhouse gas.